High strain rate behaviour of different types of chocolate. (June 2023) - Kumbár, Vojtěch; Trnka, Jan; Kouřilová, Veronika; Dufková, Renáta; Votava, Jiří; Nedomová, Šárka; Hřivna, Luděk; Polcar, Adam; Buchar, Jaroslav
Abstract: The mechanical behaviour of five different chocolate types (dark, extra dark, milk, white, and ruby) at high strain rates was studied. The experimental arrangement known as the Split Hopkinson Pressure Bar (SHPB) method was used. This experimental procedure enables to study the mechanical behaviour of materials at strain rates up to 10 3 1/s. The use of SHPB technique shows that the mechanical properties of tested chocolates significantly increase with the strain rate. This increase is much higher than that observed during the quasi static testing where the strain rate achieves values about 10 −3 1/s. Highlights: Five types of chocolate - extra dark, dark, milk, white, and even ruby, which is poor described in literature, were tested. Mechanical behaviour of chocolate was studied at high strain rates of strain (up to 2·10 3 1/s) using Split Hopkinson Pressure Bar. Resistivity of chocolate types against the high strain rate loading is: Extra Dark → Ruby → White → Milk → Dark. Values of flow stresses at high strain rates of chocolate are much higher than those obtained at the low strain rates. Dependence of flow stress on strain rate (0.002–1800 1/s) of chocolate exhibits the same features as engineering materials.